THE EFFECT OF CASH HOLDING, DEVIDEND PAYOUT RATIO, COMPANY SIZE AND COMPANY VALUE ON PROFIT EQUALIZATION - Diah Nurdiana; Desi Sunarti; Bambang Subiyanto (Jurnal Akuntansi, Keuangan, Perpajakan dan Tata Kelola Perusahaan, 2026)
Profit equalization is one of the profit management practices carried out by companies to reduce profit fluctuations so that financial performance looks more stable in the eyes of investors. This practice can be influenced by various internal factors of the company, such as the level of cash holding, dividend payout ratio, company size, and company value. This study aims to analyze the influence of cash holding, dividend payout ratio, company size, and company value on profit equalization in property and real estate companies listed on the Indonesia Stock Exchange for the 2018–2022 period. The research uses a quantitative approach with secondary data in the form of the company's annual financial statements obtained through the Indonesia Stock Exchange and the official website of each company. The research sample was determined using the purposive sampling technique so that 10 companies were obtained with a total of 50 observations. Data analysis was carried out using multiple linear regression with the help of SPSS software version 26 after going through descriptive statistical testing, classical assumption test, determination coefficient, t-test, and F test. Simultaneously, the four independent variables have a significant effect on profit equalization. These findings suggest that company characteristics, particularly company size and dividend policy, are important factors influencing companies' tendency to engage in profit equalization practices.